1991
DOI: 10.1111/j.1432-1033.1991.tb15803.x
|View full text |Cite
|
Sign up to set email alerts
|

Yeast fructose‐2,6‐bisphosphate 6‐phosphatase is encoded by PHO8, the gene for nonspecific repressible alkaline phosphatase

Abstract: Yeast fructose-2,6-bisphosphate 6-phosphatase has been purified 7000-fold by heat treatment, poly(ethy1ene glycol) precipitation, ion-exchange chromatography with Q-Sepharose Fast Flow and Mono Q followed by affinity chromatography with concanavalin-A -Sepharose and gel filtration with Superose 12. The purified dimeric enzyme contains 1.5 mol zinc and 1. Fructose 2,6-bisphosphate [Fru(2,6)Pz] plays a key role in the regulation of carbohydrate metabolism in yeast [l]. In this context the properties and the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…BAPTA, a tetravalent ion, may release these proteins from the membrane, and inhibit vacuole fusion, through its contribution to ionic strength. Vacuole fusion is commonly measured by an assay coupled to the activity of the zinc-metalloenzyme Pho8p, which is sensitive to divalent ion chelators (11). We now report that fusion assays with 5 mM Mg 2ϩ show little sensitivity to BAPTA when they are adjusted to a constant ionic strength and are performed in the presence of the heavy metal ion chelator TPEN (to obviate the effect of Zn 2ϩ chelation by BAPTA).…”
mentioning
confidence: 98%
“…BAPTA, a tetravalent ion, may release these proteins from the membrane, and inhibit vacuole fusion, through its contribution to ionic strength. Vacuole fusion is commonly measured by an assay coupled to the activity of the zinc-metalloenzyme Pho8p, which is sensitive to divalent ion chelators (11). We now report that fusion assays with 5 mM Mg 2ϩ show little sensitivity to BAPTA when they are adjusted to a constant ionic strength and are performed in the presence of the heavy metal ion chelator TPEN (to obviate the effect of Zn 2ϩ chelation by BAPTA).…”
mentioning
confidence: 98%
“…rALPase (optimum pH 8) encoded by PHO8, which is also a glycoprotein, is located in the vacuole (Clark et al, 1982) and cleaves diverse substrates to retrieve phosphate from intracellular products. It was suggested that the most important substrate of Pho8p is fructose-2, 6-bisphosphate (Plankert et al, 1991).…”
Section: The Genes and Proteins Concerning Phosphorous Metabolismmentioning
confidence: 99%
“…In S. cerevisiae, it is thought that polyP synthesis requires energy generated from glycolysis because polyP accumulation was affected by sugar concentration in the medium (Werner et al, 2005). It was also reported that fructose-2,6-bisphosphate 6-phosphatase, which controls glycolysis, was encoded by the PHO8 gene (Plankert et al, 1991). Thus, the possibility remains that Pho8p links polyP metabolism with glycolysis.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that ALP, encoded by a PHO8 gene, had substrate specificity for sugar phosphates, such as glucose-6-phosphate, fructose-2,6-bisphosphate, fructose 1,6-diphosphate (Plankert et al, 1991;Toh-e et al, 1976), phosphoprotein, and phosphopeptide (Donella-Deana et al, 1993). In S. cerevisiae, it is thought that polyP synthesis requires energy generated from glycolysis because polyP accumulation was affected by sugar concentration in the medium (Werner et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation